Size effects of potato waste on its treatment by microbial fuel cell. Issue 10 (18th May 2016) - Du, Haixia; Li, Fusheng
ABSTRACT: The performance of microbial fuel cell (MFC) in treating potato cubes with different sizes (the edge size of 3, 5 and 7 mm) was investigated. Current density was found lower as the size of potato cubes increased, even if the differences in their removal were less apparent. At the end of MFC operation for 81 days, both total and soluble chemical oxygen demand reached nearly identical values, irrespective of the potato sizes; and citrate and isobutyrate were two major organic acids remaining in the solutions. Bacterial community analysis using polymerase chain reaction, denaturing gradient gel electrophoresis and sequencing indicated that bacterial species on the anode and in the anodic solution were similar and did not change obviously with potato sizes, and that, in similarity with previous studies on potato-processing wastewater treatment, Proteobacteria and Firmicutes were two dominating phyla. Geobacter was found richer on the anode than in the anodic solutions.